KEBIJAKAN PELALAWAN LANCAR OLEH PEMERINTAH KABUPATEN PELALAWAN TAHUN 2019 - Murni Tambunan; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Road infrastructure development is one of the public interests that greatly influences the welfare of the community. The road infrastructure development policy is a development priority in Pelalawan Regency with the Pelalawan Lancar Program. Pelalawan Lancar is an effort to strengthen and expand the development of transportation infrastructure to create a smooth flow of people and goods, as well as to accelerate the provision of basic infrastructure in villages and sub-districts. The problem in this study is the Pelalawan Lancar policy in Pelalawan Regency in 2019 which has not been implemented properly. This can be seen from the condition of road stability in Riau Province in 2019 which placed Pelalawan Regency as the regency with the lowest steady road conditions with a percentage of road stability of only 24.70%. This study aims to determine the Pelalawan Lancar policy by the Pelalawan Regency Government and to find out the obstacles to the Pelalawan Lancar policy by the Pelalawan Regency Government in 2019. This study uses a qualitative approach and this type of research is descriptive. This research is located in Pelalawan Regency. Data collection techniques used are interviews and documentation. This study uses the theory of Public Policy according to William Dunn by looking at the stages of Public Policy Making, namely: 1) Agenda Setting Stage, 2) Policy Formulation Stage, 3) Policy Adoption Stage, 4) Policy Implementation Stage, 5) Evaluation Stage Policy. The results of the study indicate than the Pelalawan Lancar policy by the Pelalawan Regency government has not been implemented properly. In terms of policy, road infrastructure development has been good, but there are obstacles that have caused road infrastructure development policies to have not been fully realized. The main obstacle to road infrastructure development policy in Pelalawan Regency is the budget. Then the vehicle capacity that exceeds the limit adds to road damage in Pelalawan Regency. Keywords: Policy, Pelalawan Lancar, Development, Road Infrastructure